The Association of Intrapair Birth-Weight Differences With Internalizing and Externalizing Behavior Problems. (12th April 2018) - Tore, Elena C.; Antoniou, Evangelia E.; Reed, Keith; Southwood, Taunton R.; Smits, Luc; McCleery, Joseph P.; Zeegers, Maurice P.
Abstract : Problem behaviors are of increasing public health concern. Twin studies have revealed substantial genetic and environmental influences on children's behavior, and examining birth-weight difference could allow the identification of the specific contribution of multiple non-shared prenatal environmental factors. The Twins and Multiple Births Association Heritability Study, a UK, volunteer-based study, recruited mothers of twins aged 18 months to 5 years; 960 twins (480 pairs) were included in the analysis. Twins' mothers answered questions relative to their pregnancy and their twins' characteristics, and completed the Child Behavior Checklist (CBCL) 1½–5. The association between the absolute birth-weight difference and each CBCL scale's score difference was analyzed by means of multiple linear regressions. Expected mean CBCL score differences were calculated. In monozygotic (MZ) twins, statistically and clinically significant associations were found between intrapair birth-weight difference and difference in total problems, internalizing problems, and emotional reactiveness. No significant results were observed neither in dizygotic (DZ) twins when analyzed as a separate group nor in MZ and DZ twins combined. The results of the present study suggest that with increasing the absolute birth-weight difference, the intrapair difference in total problems, internalizing behaviors and emotionality increases, with smaller twins being at major risk for later behavior problems. Moreover, these results suggest a causal association between birth weight and behavior development.